Effects of Aspergillus spp. Phospholipase to Induce Histological and Biochemical Changes in Male Rats - T. Jasim, Saif; Hamad Saleh, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
This study was achieved to exhibit the effects of Aspergillus spp. phospholipase on rats (in vivo). In this study, 18 adult albino male rats were used, which were divided into three groups including the control group (received ad libitum), the second group (injected with 0.05 ml/animal of phospholipase), and the third group (injected with 0.1 ml/animal of phospholipase) for 3 weeks. The results showed a highly significant increase (p